European Resuscitation Council Guidelines 2021: Cardiac arrest in special circumstances. (April 2021) - Lott, Carsten; Truhlář, Anatolij; Alfonzo, Annette; Barelli, Alessandro; González-Salvado, Violeta; Hinkelbein, Jochen; Nolan, Jerry P.; Paal, Peter; Perkins, Gavin D.; Thies, Karl-Christian; Yeung, Joyce; Zideman, David A.; et al.
Abstract: These European Resuscitation Council (ERC) Cardiac Arrest in Special Circumstances guidelines are based on the 2020 International Consensus on Cardiopulmonary Resuscitation Science with Treatment Recommendations. This section provides guidelines on the modifications required to basic and advanced life support for the prevention and treatment of cardiac arrest in special circumstances; specifically special causes (hypoxia, trauma, anaphylaxis, sepsis, hypo/hyperkalaemia and other electrolyte disorders, hypothermia, avalanche, hyperthermia and malignant hyperthermia, pulmonary embolism, coronary thrombosis, cardiac tamponade, tension pneumothorax, toxic agents), special settings (operating room, cardiac surgery, catheter laboratory, dialysis unit, dental clinics, transportation (in-flight, cruise ships), sport, drowning, mass casualty incidents), and special patient groups (asthma and COPD, neurological disease, obesity, pregnancy).